Correlation of Metabolomics and Functional Foods Research in 2020 to 2023: Bibliometric Analysis - Dewi, Nazmah Sefriani (Bumi Publikasi Nusantara, 2025)
This research was conducted to determine the development of research on metabolomics and functional food using bibliometric analysis including analysis of top citations, and publishers, visualization of the most productive authors, and a map of publication development based on keywords. This research method is descriptive quantitative with bibliometric analysis using Publish or Perish software for data collection and VOSviewer to visualize related research terms. Data collection was carried out by searching the Google Scholar database with the keywords